Implementation of Sociological Principles in the Development of Islamic Religious Education Curriculum - Firmansyah, Firmansyah; Hamami, Tasman; Elysa, Ratianarimamy Niriko; Kiryakova, Gabriela (Yayasan Cendekia Gagayunan Indonesia, 2025)
Islamic education is experiencing dynamic development in line with social changes in society, so it demands the development of a curriculum that is relevant and based on strong principles. One of the important principles in curriculum development is sociological principles, which link education and the needs of society. This research aims to analyze the contribution of sociological principles in the development of Islamic religious education curriculum. The method used is descriptive qualitative research with a library research approach. Data were collected from a variety of related literature and analyzed descriptively with a systematic and objective presentation. The results of the study show that sociological principles play a significant role in designing the Islamic religious education curriculum to be able to respond to the needs and challenges of the community. A curriculum developed based on this principle can form students who not only understand religious values, but also have social awareness, ethics, and norms that apply in society. Thus, the application of sociological principles in the development of Islamic religious education curriculum allows the creation of contextual learning that is in harmony with the social dynamics of Islamic society.